Barcelona, a musical olympus? Live concerts, club cultures, television and city branding. (2nd January 2020) - Wheeler, Duncan
ABSTRACT: The 1992 Barcelona Olympic Games announced Spain's democratic credentials and facilitated a vast urban regeneration project in the Catalan capital. There is extensive bibliography on the role played by culture in the forging of the so-called Barcelona model, but little attention has been paid thus far to popular music. Barcelona may lack Ibiza's super-clubs, but, in the space of a generation, the city has gone from being a relative backwater to becoming a staple of major international tours, and music has increasingly become a popular tourist attraction. This is a logical albeit not necessarily intended consequence of Barcelona's Olympic adventure. I begin with a preliminary survey of rock and pop concerts before exploring in the main section how and why live and recorded music performed a key but underexplored role in the success of the 1992 Olympic Games. A critical examination of the subsequent development of popular music in the Catalan capital will provide a means by which to grapple with the legacy of the Transition and Barcelona '92 in post-recession Spain.